á¹¢uwar al-á¸¥aá¸Änah baâ€˜da al-á¹alÄq fÄ« Aceh al-Wusá¹Ã¡ - Fauzi, Fauzi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
The divorce rate occurred in post-tsunami Aceh have increased sharply, especially in Central Aceh district by 2015. This research was conducted in order to figure out the causes of divorce, the patterns of á¸¥aá¸Änah (child custody) and the parentâ€™s attention towards their children after the divorce. The selection of Central Aceh as the object of research was because this district has been occupying the highest position of divorce rate when compared to other districts/cities. The results of this study explain that divorce occurs due to love affairs, economic problems, third-party intervention, early marriage, lack of communication, having no trust and different views of life principles. Meanwhile the pattern of á¸¥aá¸Änah happened was mostly carried out by their mother, and the rest was taken care of by their father and the third party like their grandparents. The relationship between the cause of divorce and á¸¥aá¸Änah is that when divorce is caused by a spouseâ€™s bickering usually has a negative effect on the pattern of á¸¥aá¸Änah, if the divorce happened due to disagreement in the life principles or a certain principle it would have a positive impact. This negative impact on certain conditions requires that older children bear the needs of their younger siblings.DOI:Â 10.15408/sdi.v24i1.4189